МОНГОЛЫН ИРГЭНИЙ НИЙГМИЙН ХӨГЖЛИЙН СОРИЛТ БЭРХШЭЭЛ, БОЛОМЖ НӨХЦӨЛ - Д.Мягмарсүрэн; Я.Төгөлдөр (Politology, 2023)
This article aims to describe and define the developmental phases of Mongolia’s civil society during the last 30 years periodically. This study examined the challenges the civil society has encountered and overcome in the unique social and cultural context of post-communist Mongolia during those 30 years of parallel transition to democratization and market economy. It investigated what opportunities and situations for creating citizens with Mongol identity have been produced by the external factors such as democratic reform, market economy, legal changes, sudden boom and decline of mining sector, and traditional life and culture.